Comparison of Y-jet and OIL effervescent atomizers based on internal and external two-phase flow characteristics - Mlkvik Marek; Zaremba Matous; Jedelsky Jan; Jicha Miroslav (EPJ Web of Conferences, 2016)
Presented paper focuses on spraying of two viscous liquids (μ = 60 and 143 mPa·s) by two types of twinfluid atomizers with internal mixing. We compared the well-known Y-jet atomizer with the less known, “outside in liquid” (OIL), configuration of the effervescent atomizer. The required liquid viscosity was achieved by using the water-maltodextrin solutions of different concentrations. Both the liquids were sprayed at two gas inlet pressures (Δp = 0.14 and 0.28 MPa) and various gas-to-liquid ratios (GLR = 2.5%, 5%, 10% and 20%). The comparison was focused on four characteristics: liquid flow-rate (for the same working regimes, defined by Δp and GLR), internal flow regimes, Weber numbers of a liquid breakup (We) and droplet sizes. A high-speed camera and Malvern Spraytec laser diffraction system were used to obtain necessary experimental data. Comparing the results of our experiments, we can state that for both the liquids the OIL atomizer reached higher liquid flow-rates at corresponding working regimes, it was typical by annular internal flow and higher We in the near-nozzle region at all the working regimes. As a result, it produced considerably smaller droplets than the second tested atomizing device, especially for GLR < 10%.